2016
DOI: 10.3168/jds.2015-10412
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily milking during late lactation in pasture-fed dairy cows has minor effects on feed intake, body condition score gain, and hepatic gene expression

Abstract: Milking cows once daily (1×) is a management practice occasionally used during mid/late lactation in pasture-based systems. It has been postulated that 1× milking will reduce dry matter intake (DMI) and increase body condition score (BCS) gain; however, this has not been quantified. Lactating, pregnant Holstein-Friesian dairy cows (n=52) were allocated to either 1× or twice-daily (2×) milking in mid-January (summer, 175d in milk). To obtain accurate DMI measurements, cows underwent 4 periods in a Calan gate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Interestingly, FS-3-in-2 yielded similar lactation yield percentage changes to short-term (3-8 wk) use of OAD in early lactation (Phyn et al, 2014;Kennedy et al, 2021), while requiring considerably fewer milkings, a result also reported by Woolford et al (1985). Previous studies (e.g., Grala et al, 2016) using OAD in late lactation have not included production information before the experimental period, meaning the effect on lactation yield cannot be discussed in relation to our results.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, FS-3-in-2 yielded similar lactation yield percentage changes to short-term (3-8 wk) use of OAD in early lactation (Phyn et al, 2014;Kennedy et al, 2021), while requiring considerably fewer milkings, a result also reported by Woolford et al (1985). Previous studies (e.g., Grala et al, 2016) using OAD in late lactation have not included production information before the experimental period, meaning the effect on lactation yield cannot be discussed in relation to our results.…”
Section: Discussionmentioning
confidence: 86%
“…Variations to the traditional twice-daily milking regimen have become important in some production systems: some farms have instituted once-daily milking (Clark, Phyn, Tong, Collis, & Dalley, 2006;Grala et al, 2016), some farms use asymmetrical twice-daily milking such as alternating 14 and 10 hr inter-milking intervals (Chládek et al, 2014;Rémond, Pomiès, Julien, & Guinard-Flament, 2009), some farms have moved to thrice-daily milking (Allen, DePeters, & Laben, 1986), and robotic milking introduces randomness into the milking frequency (Løvendahl & Chagunda, 2011). In our model, when the duration of the inter-milking interval and the milking frequency were included in the sensitivity analysis, these factors were the dominant effects on both the milk drug concentrations and drug persistence.…”
Section: Identifiability Of the Model Parameters Is A Major Consideramentioning
confidence: 99%
“…In early lactation cows, ODM management improved the nutritional status of the animals as they lost less live weight and body condition than those under TDM and thus improved their energy balance 8,9 . In late lactation cows in pasture-fed, ODM milking showed a minor effects on feed intake and body condition score gain 10 .…”
Section: Introductionmentioning
confidence: 96%